Comparison of efficacy and safety between electroacupuncture at 'four sacral points' and conventional electroacupuncture for the treatment of urinary incontinence after stroke: study protocol for a randomised controlled trial. Issue 11 (5th November 2018) - Chen, Shan; Wang, Siyou; Xuan, Lihua; Lu, Hanti; Hu, Zhikai; Zhang, Chao; Zhang, Huifang
Abstract : Introduction: Electroacupuncture at 'four sacral points', also known as electrical pudendal nerve stimulation therapy, combines the advantages of pudendal nerve neuromodulation and the technique of deep insertion of long acupuncture needles. It has been used to treat stress urinary incontinence, female urgency-frequency syndrome, idiopathic urgency urinary incontinence and neurological bladders in previous studies. Here, we describe the protocol for a randomised controlled trial for evaluation of the efficacy and safety of electroacupuncture at 'four sacral points' for the management of urinary incontinence after stroke. Methods and analysis: This is an open-label randomised controlled trial with blinded assessments and analyses. A total of 140 eligible patients will be randomly allocated to two groups. The treatment group (n=70) will receive electroacupuncture at 'four sacral points' along with routine medical care, while the control group will receive conventional electroacupuncture along with routine medical care. Twenty treatment sessions will occur over a period of 4 weeks. The primary outcome measures will be the self-recorded findings in an incontinent episode diary at baseline and at 4 weeks after baseline. The secondary outcome measures will be the International Consultation on Incontinence Questionnaire Urinary Incontinence—Short Form (ICIQ-UI SF) score and the Barthel Activities of Daily Living Index (Barthel ADL Index) score at baseline and at 4 and 28 weeks after baseline. Ethics and dissemination: This protocol has been approved by the Ethics Committee of the First Affiliated Hospital of Zhejiang Chinese Medical University (approval No. 2018-K-059–01). Written informed consent will be obtained from each participant. The results of the study will be published in peer-reviewed journals. Trial registration number: ChiCTR-IOR-17012847; Pre-result.